2022
DOI: 10.1093/jpids/piac036
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Cystic Fibrosis Lung Microbiome: Making the Most of a Sticky Situation

Abstract: Chronic lower respiratory tract infections are a leading contributor to morbidity and mortality in persons with cystic fibrosis (pwCF). Traditional respiratory tract surveillance culturing has focused on a limited range of classic pathogens; however, comprehensive culture and culture-independent molecular approaches have demonstrated complex communities highly unique to each individual. Microbial community structure evolves through the lifetime of pwCF and is associated with baseline disease state and rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 110 publications
4
15
0
Order By: Relevance
“…Finally, our study was the first to associate sinus microbiome compositional structure with sinonasal clinical outcomes by transplant status in PwCF as noted by patient reported questionnaires. Not surprisingly, those with greater microbial diversity had improved symptom scores consistent with earlier findings 25 . Finally, we did not observe a significant association with LM scores and microbiome composition and were likely limited by sample size similar to others 26,27 …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Finally, our study was the first to associate sinus microbiome compositional structure with sinonasal clinical outcomes by transplant status in PwCF as noted by patient reported questionnaires. Not surprisingly, those with greater microbial diversity had improved symptom scores consistent with earlier findings 25 . Finally, we did not observe a significant association with LM scores and microbiome composition and were likely limited by sample size similar to others 26,27 …”
Section: Discussionsupporting
confidence: 87%
“…Not surprisingly, those with greater microbial diversity had improved symptom scores consistent with earlier findings. 25 Finally, we did not observe a significant association with LM scores and microbiome composition and were likely limited by sample size similar to others. 26,27 Previous studies have demonstrated the sinonasal cavity as an initial site of bacterial colonization, including canonical pathogens such as P. aeruginosa, with development of a microbial reservoir that can then seed the lungs of PwCF.…”
Section: Discussionsupporting
confidence: 48%
“…The respiratory microbiota profile is altered in infants with CF, independent of the presence of pathogens detected with culture-based techniques [14][15][16][17] . Early microbial development is characterized by early dominance and persistence of Staphylococcus aureus in infants with CF, shifting to Corynebacterium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many external genetic factors and genotypic variants of CF contribute to the disease phenotype of the CF individual that make it very difficult to create a universal treatment solely based on host genotype or phenotype (5). Beyond CFTR modulators and broad antibiotic treatments directed at common CF airway pathogens, insights may be gained in observing the variation in the CF airway microbiome across clinical states (6)(7)(8)(9). More recent work also suggests that the metabolome could be used to predict or diagnose pulmonary exacerbation (10,11).…”
Section: Introductionmentioning
confidence: 99%